Syncope with Surprise: An Unexpected Finding of Huge Gastric Diverticulum - Mauro Podda; Jenny Atzeni; Antonio Messina Campanella; Alessandra Saba; Adolfo Pisanu (Case Reports in Surgery)
A gastric diverticulum is a pouch protruding from the gastric wall. The vague long clinical history ranging between dyspepsia, postprandial fullness, and upper gastrointestinal bleeding makes this condition a diagnostic challenge. We present a case of large gastric diverticulum that has been diagnosed during clinical investigations for suspected cardiovascular issues in a patient admitted at the medical ward for syncope. A 51-year-old man presented to the medical department due to a syncopal episode occurring while he was resting on the beach after having his lunch, with concomitant vague epimesogastric gravative pain without any other symptom. A diagnosis of neuromediated syncopal episode was made by the cardiologist. Due to the referred epimesogastric pain, an abdominal ultrasound scan was carried out, showing perisplenic fluid. A CT scan of the abdomen was performed to exclude splenic lesions. The CT scan revealed a large diverticulum protruding from the gastric fundus. The upper gastrointestinal endoscopy visualized a large diverticular neck situated in the posterior wall of the gastric fundus, partially filled by undigested food. The patient underwent surgery, with an uneventful postoperative course. Histologic examination showed a full-thickness stomach specimen, indicative of a congenital diverticulum. At the 2nd month of follow-up, the patient was asymptomatic.